2010
DOI: 10.5380/rf.v40i4.20336
|View full text |Cite
|
Sign up to set email alerts
|

Influência Do Tamanho E Forma Da Unidade Amostral Sobre a Estrutura De Dependência Espacial Em Quatro Formações Florestais Do Estado De São Paulo

Abstract: O tamanho e forma da unidade amostral tem grande influência na percepção da autocorrelação espacial. Dessa forma, a escolha de uma escala adequada para o estudo de processos espaciais é extremamente importante, pois a dinâmica espacial pode ser considerada significante, insignificante ou inoperante a depender da escala utilizada ou, ainda, as relações entre as variáveis podem ser obscurecidas ou distorcidas. O objetivo deste trabalho foi estudar, por meio de técnicas geoestatísticas baseadas em modelos, a estr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(24 reference statements)
1
3
0
1
Order By: Relevance
“…Similar behavior was observed by Oda-Souza et al (2010) in four forest formations in São Paulo state, Brazil, and by Bellehumeur et al (1997) when they evaluated the density of species in a Malasian tropical forest.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Similar behavior was observed by Oda-Souza et al (2010) in four forest formations in São Paulo state, Brazil, and by Bellehumeur et al (1997) when they evaluated the density of species in a Malasian tropical forest.…”
Section: Discussionsupporting
confidence: 83%
“…Due to the sample grid configuration, with predominance of one-direction points (East-West), the semivariograms presented small number of values observed to consider the 50 x 50 m sample units as the most suitable. In this sense, Oda-Souza et al (2010) observed that the spatial dependence of the variable biomass was intensified with the increase in square sample units which was not seen in rectangular sample units.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Studies in the present literature have assessed the use of classical spatial sampling schemes, including random, centered systematic, triangular, hexagonal and stratified schemes, for experimental planning in order to find information that may support an efficient description of spatial variability in the georeferred data (McBratney et al, 1981;Yfantis et al, 1987, Oda-Souza et al, 2010. Nevertheless, with the acceptance of variations in the parameters and characteristics that support the spatial process, such as the nugget, sill, range and anisotropy effects, the sampling schemes described above have generated very unreliable results (Yfantis et al, 1987;Dunn and Harisson, 1993;Diggle and Ribeiro Junior, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Esses valores podem ter sido influenciados, dentre uma série de outros fatores, pela forma retangular dos 1,02 ha amostrados, uma vez que áreas com esse desenho possuem um maior efeito de borda e representam melhor os efeitos dos gradientes na composição da vegetação do que amostras quadradas ou circulares (FELFILI; CARVALHO; HAIDAR, 2005; FELFILI et al, 2011), portanto, áreas quadradas tendem a descrever melhor a estrutura e formas retangulares a variação na vegetação (ODA-SOUZA et al, 2010), o que pode ajudar a explicar o fato de a curva espécies/área não ter mostrado tendência à estabilização (Figura 2), sendo que a partir da 51º parcela, 17 espécies (22%) foram acrescidas.…”
Section: Resultsunclassified